Public Knowledge of Cardiovascular Diseases and its Risk Factors in Makkah City, Saudi Arabia - Alabdali, Samer; Aljahdali, Shahad; Alghamdi, Donia; Alahmadi, Nawaf; Alqarni, Aljauhra; Alluqmani, Ghassan; Alahmadi, Ahmad; Mandourah, Anmar (Saudi Medical Horizons Journal, 2025)
Background and aim: Cardiovascular diseases (CVDs) are among the leading causes of death globally, with both modifiable and non-modifiable risk factors playing major roles in their development. Limited research exists on public awareness of CVDs in Makkah, Saudi Arabia. This study aims to assess the level of knowledge regarding CVDs and their risk factors among the adult population in Makkah. Methods: A descriptive cross-sectional study was conducted between January and April 2025 among the general population in Makkah City. Data were collected using a validated Arabic-based, self-administered online questionnaire. Participants included residents aged 18 and above from various educational and occupational backgrounds. Results: A total of 676 participants were participated, with 63.2% being female. The majority (38.3%) were aged 18–25 years, and 74.0% held a university degree. Most respondents (94.8%) were Saudi nationals. Although 91.7% had heard of heart attacks, only 57.4% demonstrated good overall knowledge of CVDs and their risk factors. Notably, those with higher education levels, CPR training, or prior CPR experience showed significantly better awareness. Conclusion: Despite high exposure to general CVDs information, many participants displayed limited understanding of less common symptoms and specific risk factors. Educational efforts, particularly those incorporating cardiopulmonary resuscitation (CPR) training, withtargeting younger and less-informed groups, are essential to improve public awareness and reduce the risk of CVDs.